UJI TANAH DAN PENANAMAN UNTUK MENILAI TINGKAT KESUBURAN TANAH - Priyono - (Eksplorasi, 2004)
Field experiment was conducted during 3,5 months (April-August 2002) to determine soil and plant testing evaluateed degree of soil fertility at Kaling village, Tasilmadu Sub district, Karanganyar district. The experiment used Randomized Completely Block Design with 4 replications The treatmenths used on factor was organic fertilizer (solid waste of sugar factory); pH, N-total, P-Bray, K, Ca, Mg, H, Al, CEC, Base saturation, and economic analysis (BC ratio, income statement). Result showed that the effect of organic fertilizer nonsignificant was whole parameters: the height of plant, the weight of 100 dry seeds, the weight of dry seeds, the fresh weight of biomass, the fresh weight body plant, the number of empty pod, except the dry weight of biomass. Nevertheless to whole data was received to trend increasing of the whole parameters, except the numbers of empty pod. Soil condition before was planted (was not planted) very poor, and then after was planted the soil condition is very fertility. After account economic was received BC ratio ± 1.55 and income statement Rp 647.500,00/3 months. Conclusion this experiment is follow up to coming. Keywords : Testing of soil and planting, soil analysis, economic analysis, planting, soil fertility.